Application Of The Profile Matching Method In The Selection Of New Students For Batak Karo Bridal Makeup Skills In The PKK Program - Suma Dia Syahwani; Maulita, Yani; Syari, Mili Alfhi (Yayasan Kita Menulis, 2023)
Makeup is the art of using makeup materials to change the natural face shape into an artistic face. Work Skills Education (PKK) itself is an education and training service program oriented towards the development of work skills provided to students in order to have competence in certain skills that are in accordance with job opportunities. Profile matching is the process of comparing the actual data value of a profile to be assessed with the expected profile value so that it can be known the difference in competence or the distance between one value and another. This research aims to facilitate the selection of new prospective students in the PKK program at the Pelawi Salon Binjai Course and Training Institute (LKP) and optimize admin work time in the process of selecting new students. By applying this method, it aims to see the eligibility of prospective students according to predetermined criteria so that the opportunity to take part in the PKK program can be received by the right person. There are 5 sample data with 6 criteria in this research, the final result in this study is 3.5 being the highest value and 2.99 being the lowest value.